Effect of percentage of polyvinyl alcohol on the properties of econazole nitrate polymeric micelles eye drop - Ali Hameed; Athmar Dh. H. Al-Shohani; Safar M. Alqahtani (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Econazole nitrate, a chemically produced triazole drug, is utilized to manage fungal keratitis. It has potent antifungal properties against many species; the readily available formula exhibits inadequate corneal permeability, visual aberrations, excessive tearing, dilution of tears, and leakage via the nasolacrimal duct.